Unpacking Auditor Performance: The Influence of Internal Locus of Control, Salary, and the Moderating Role of Spiritual Intelligence - Mujiatun, Siti; ., Rahmayati; Badawi, Afif (Journal of Ecohumanism, 2024)
This study aims to investigate how internal locus of control and auditor salaries influence auditor performance, with a focus on spiritual intelligence as a moderating factor. The research was conducted among auditors at a Public Accounting Firm in Indonesia. Using purposive sampling, a sample of 92 auditors was selected, and data collection was carried out through a survey. The data were analyzed through Multiple Linear Regression and Moderated Regression Analysis (MRA). The results indicate that both internal locus of control and salary positively impact auditor performance. Furthermore, the findings reveal that spiritual intelligence strengthens the link between internal locus of control and auditor performance. However, when examining the moderation of intelligence with auditor salaries, the results show that intelligence weakens the relationship between auditor salaries and performance.